COMPUTER BUSINESS SIMULATION AS AN INTERACTIVE FOREIGN LANGUAGE TEACHING TOOL: POTENTIAL FOR APPLICATION IN A HIGHER EDUCATION CURRICULUM - N. Moskovskaya; E. Perova (Вестник Северо-Кавказского федерального университета)
The relevance of the chosen topic is due to the need to introduce interactive educational tools in the methodology of teaching foreign language for professional purposes. The objective of this paper is to assess the effectiveness of computer business simulation as an interactive foreign language teaching method in a university curriculum. The article provides the updated classification of educational digital games introduced by the Directorate General for Education and Culture of the European Commission. The implementation of some popular educational computer business-simulations is outlined and their educational value in a university setting is discussed. The important inding of this research is the ability of simulation to encourage students to apply their functional expertise to professional communication in a foreign language.